Development of comprehensive fire and explosion risk assessment on coal reclaim tunnel using Monte Carlo simulation and risk matrix method. Issue 4 (15th November 2021) - Widodo, Nuhindro Priagung; Permadi, Dimas Agung; Ihsan, Ahmad; Kusuma, Ginting Jalu
Abstract: The new comprehensive fire and explosion risk assessment of coal reclaim tunnel (CRT), by applying Monte Carlo simulation to address the probability distribution of risk fire and explosion factor, and the risk matrix analysis as a method to classify the total risk rating obtained from Monte Carlo simulation, has been proposed in the present research. Two CRT facilities, that is A and B, which differentiate by the locations have been analyzed using the proposed method. The result shows that CRT A is classified as extreme risk level, and CRT B is divided into two groups, which classified as high‐risk level with cumulative probability of 81.73% and as moderate risk level with cumulative probability of 18.27%. Because they situated on the extreme risk and high‐risk level, the risks are classified in unacceptable risk level. After simulating with several preventive actions, the result shows that the risks have been lowered into acceptable risk level, with a 100% probability of moderate‐risk level. A sensitivity analysis for the CRT A and B reveals that among 49 factors identified, the 4 (four) most influential factors for the fire and explosion risk are the ventilation system, the oxygen concentration, a coal spontaneous combustion, and the monitoring facilities. Abstract : The risk assessment method developed in this research has been beneficial in inspecting the explosion potential of coal reclaim tunnel facilities, considering all the factors causing an explosion that has been analyzed simultaneously and comprehensively. Several factors that cause fires and explosions at the CRT facility have an un‐normal distribution. By applying the Monte Carlo simulation, the severity and probability levels can be described in more detail and can be evaluated in safety risk matrix to determine the explosion risk level.